"At One Point We Had No Funding for Paper": How Grants and the Covid Crises Have Shaped Service Provision in Child Advocacy Centers. Issue 1 (1st January 2023) - Addison, Kalysta; Rubin, Zach
ABSTRACT: The confluence of the two major challenges has combined to create special challenges for rural nonprofits serving victims of crime: the fluctuation of federal funding, and the Covid-19 pandemic. We discuss the challenges faced by Child Advocacy Centers in northwestern South Carolina in the context of these shifting challenges. From qualitative interviews conducted at 14 centers in this primarily rural region, we explain the challenges they face and the potential effects on the communities they serve interpreted through the lens of Resource Dependence Theory, which predicts that organizations reduce uncertainty of funding through increasing their partnership bonds with cooperative entities.